Failing to plan is planning to fail: advance care planning for people nearing the end of life. (October 2011) - Newman, Rachel; Thomas, Keri
Following the inaugural meeting in Melbourne, Australia, in 2010, the newly formed International Society for Advance Care Planning and End of Life Care (ACPEL) held its second International 3-day conference in London in June this year, hosted by the UK team of which Keri Thomas was convenor. This article gives an overview of the conference and one delegate''s perspective (R Newman). With over 400 delegates from across the world representing 22 different countries, the conference and society represent the increasing international recognition of the importance of holding and recording advance care planning discussions with people nearing the end of their lives, with a particular focus on the growing needs of the elderly in our society.